2012
DOI: 10.1371/journal.pone.0048010
|View full text |Cite
|
Sign up to set email alerts
|

Endophyte-Mediated Effects on the Growth and Physiology of Achnatherum sibiricum Are Conditional on Both N and P Availability

Abstract: The interaction of endophyte–grass associations are conditional on nitrogen (N) availability, but the reported responses of these associations to N are inconsistent. We hypothesized that this inconsistency is caused, at least in part, by phosphorus (P) availability. In this experiment, we compared the performance of endophyte-infected (EI) and endophyte-free (EF) Achnatherum sibiricum subjected to four treatments comprising a factorial combination of two levels of N (N+ vs. N−, i.e. N supply vs. N deficiency) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 56 publications
(61 reference statements)
1
25
0
1
Order By: Relevance
“…Under LN conditions, this positive effect was weaker, while E+ plants did show a higher aboveground biomass than E− plants. This was similar to a previous study using A. sibiricum (Li Ren, Han, Yin, Wei, & Gao 2012). Under nitrogen deficiency, the N concentration was lower for E+ compared to E− plants; however, E+ plants had an elevated photosynthetic capacity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under LN conditions, this positive effect was weaker, while E+ plants did show a higher aboveground biomass than E− plants. This was similar to a previous study using A. sibiricum (Li Ren, Han, Yin, Wei, & Gao 2012). Under nitrogen deficiency, the N concentration was lower for E+ compared to E− plants; however, E+ plants had an elevated photosynthetic capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Achnatherum sibiricum plants with a higher PNUE could be the result of investing relatively more of their N in photosynthetic machinery (Li et al. 2012). Previous reports have also indicated that organisms with a greater growth advantage in nutrient‐poor conditions are those that are able to modify their body nutrient content and increase the efficiency of nutrient use without major decreases in their growth rates (Elser et al., 2003; Mulder & Bowden, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms have not been tested but the authors speculate about increased P solubilisation. Li et al ( 2012 ) found an interaction between N and P availability for endophyte-grass symbiosis: the endophyte infection improved acid phosphatase activity of endophyte-plants but only when suffi cient nitrogen was available. Saprophytic fungi can stimulate organic matter decomposition and thus increase nutrient availability for the plants ( Buée et al 2009 ).…”
Section: Nutrientsmentioning
confidence: 96%
“…Several studies have also reported greater number of tillers in endophyte-infected than endophyte-free plants of some genotypes in [6,18,25,33,34]. In contrast, Cheplick [35] found less number of tillers, leaf area and biomass in some endophyte-infected genotypes of perennial ryegrass than in endophyte-free plants under both irrigated and drought conditions.…”
Section: Main Effects Of Endophyte Cultivar and Water Regimesmentioning
confidence: 98%
“…Tropical forage grasses are grown on marginal lands with limited or no agricultural inputs and their growth and survival depends on a wide range of environmental stresses [16]. Previous studies have investigated the role of A. implicatum mainly for its biocontrol property against pathogens such as Drechslera fungal pathogen in Brachiaria and against Meloidogyne incognita in tomato [1,17,18]. There has not been any detailed study on the effects of A. implicatum on morpho-physiological responses of Brachiaria under drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%